A Single Conserved Residue Mediates Binding of the Ribonucleotide Reductase Catalytic Subunit RRM1 to RRM2 and Is Essential for Mouse Development - Specks, Julia (Mol Cell Biol, 2015)
The ribonucleotide reductase (RNR) complex, composed of a catalytic subunit (RRM1) and a regulatory subunit (RRM2), is thought to be a rate-limiting enzymatic complex for the production of nucleotides. In humans, the Rrm1 gene lies at 11p15.5, a tumor suppressor region, and RRM1 expression in cancer has been shown to predict responses to chemotherapy. Nevertheless, whether RRM1 is essential in mammalian cells and what the effects of its haploinsufficiency are remain unknown. To model RNR function in mice we used a mutation previously described in Saccharomyces cerevisiae (Rnr1-W688G) which, despite being viable, leads to increased interaction of the RNR complex with its allosteric inhibitor Sml1. In contrast to yeast, homozygous mutant mice carrying the Rrm1 mutation (Rrm1(WG/WG)) are not viable, even at the earliest embryonic stages. Proteomic analyses failed to identify proteins that specifically bind to the mutant RRM1 but revealed that, in mammals, the mutation prevents RRM1 binding to RRM2. Despite the impact of the mutation, Rrm1(WG/+) mice and cells presented no obvious phenotype, suggesting that the RRM1 protein exists in excess. Our work reveals that binding of RRM1 to RRM2 is essential for mammalian cells and provides the first loss-of-function model of the RNR complex for genetic studies.